The dynamics of changes of regional and all-Russian identities in the polynational region (based on the ethnosociological studies in the republic of Bashkortostan in 1990-2014) - S. S. Alexeenko; F. G. Safin; A. I. Khaliulina (Научный вестник МГТУ ГА)
The article is devoted to the process of assuming sovereignty and post-Soviet development of national republics within the Russian Federation which made profound changes in the sphere of national and civil identity. The article reveals the role of the linguistic factor in the formation and development of Russian identity in the multinational republic of Bashkortostan in the context of national and civil identity display depending on the social and psychological views of respondents. The main advantage is that in spite of the measures taken by the authorities of the republic to form regional identity, the results of the ethnosociological studies show that all-Russian identity of the multinational population of the republic of Bashkortostan is increasing.